A novel soft end effector with active palm and fingertips for robotic picking. (July 2023) - Guo, Canzhi; Zhang, Song; Yang, Yu; Cheng, Guanggui; Ding, Jianning
Designing a type of dexterous soft end effector is the premise to guarantee the working efficiency of a picking robot. For the practical needs of grasping flat objects on the table and unscrewing the bottle cap, we have refined the advantages of traditional soft grippers and designed a novel two-finger soft end effector with active palm and also with two active fingertips. The bending of the fingers actuated by vacuum, the palm and fingertips are driven by motors. Three grasping strategies are developed for the active fingertips so that the gripper can not only grasp flat objects on the tabletop, but also unscrew a cap of a bottle. Further, benefit from the active palm and the high stiffness design method of the finger skeleton, two working modes, pinching mode and grasping mode, have been developed for the gripper. The end effector achieves a maximum grasping force of 32 N in the horizontal direction and 28 N in the vertical direction under the air pressure of −90 kPa. The working angle of the fingers is 0 ° –120 ° . The size of the object can be grasped ranges from 0 to 200 mm in diameter. Performance verification experiment shows that the active fingertips play an important role in helping the gripper grasp thin objects such as credit cards and printing papers. Grasping experiments on different objects demonstrate that the active fingertips design significantly enhances the flexibility of the gripper and the application it can empower the manipulator.